Characterization of antibiotic resistance and virulence genes of ocular methicillin-resistant Staphylococcus aureus strains through complete genome analysis. (November 2021) - Kathirvel, Kandasamy; Rudhra, O.; Rajapandian, Siva Ganesa Karthikeyan; Venkatesh Prajna, Namperumalsamy; Lalitha, Prajna; Devarajan, Bharanidharan
Abstract: Virulence-factor encoding genes (VFGs) and antimicrobial resistance genes (ARGs) of ocular Methicillin-Resistant Staphylococcus aureus (MRSA), are the reason behind the common cause of severe and untreatable ocular infection and are largely unknown. The unavailability of the complete genome sequence of ocular MRSA strains hinders the unambiguous determination of ARGs and VRGs role in disease pathogenesis and their genomic location. To fulfill this critical need, we achieved the high-quality complete genome of four ocular MRSA strains (AMRF3 – AMRF6) by combining MinION nanopore sequencing technology, followed by polishing with Illumina sequence reads. We obtained a single chromosome and a plasmid in each strain. Sequence typing revealed that AMRF3 and AMRF5 strains harbored ST772, whereas AMRF4 and AMRF6 harbored ST 2066. All plasmids carried heavy metal cadmium resistance genes cadC and cadD, while cadA was detected only in the plasmid pSaa6159 of AMRF4 and AMRF6 strains. Further, pSaa6159 contains a complete Tn552 transposon with beta-lactamase genes, blaI, blaR1, and blaZ . Interestingly, pSaa6159 in AMRF6 carried five copies of Tn552 transposon. Several exotoxins and enterotoxins were identified across ocular MRSA strains and ST2066 strains found to be not carried any enterotoxins; this finding suggests that these two strains are exotoxigenic. Besides, ST2066 strains carried serine proteases ( splA, splB, splD, splE and spIF ) and exotoxin ( seb and set 21 ) for their virulence, while ST772 carried antimicrobial resistance genes ( blaZ, dfrG, msrA, mphC and fosB ) and enterotoxin sec for virulence, suggesting sequence type-specific resistance and virulence. Also, we identified many VFGs and ARGs, that provided multi-drug resistance, enterotoxigenic, exotoxigenic, biofilm-forming, host tissue adhesion and immune response evasion in ocular MRSA strains. Thus, our study provides a better insight into the genomes of ocular MRSA strains that would provide more effective treatment strategies for ocular MRSA infection. Highlights: We report the high-quality complete genome of four human ocular Methicillin-Resistant Staphylococcus aureus (MRSA) strains. The plasmid in each strain harbors a complete Tn552 transposon with β-lactamase genes and cadmium resistance genes. We report several strain and sequence type specific antibiotic resistance and virulence genes in ocular MRSA strains. These genes provide MDR, enterotoxigenic, exotoxigenic, biofilm-forming, host tissue adhesion and immune response evasion. This study provides a better insights into the genomes of ocular MRSA strains that would help future therapeutic strategies.